PENGAWASAN PADA OBJEK WISATA DANAU RAJA DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Myta Hartati; Siti Sofro Siddiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Supervision is all efforts and activities to identify and assess the actual reality on the implementation of tasks or activities are in accordance with rules or not. Supervision towards tourist attraction of Danau Raja is done directly by government, youth section, sports section and tourism section. In addition, supervisor coordinated with the Organization of Pancasila Youth through the MOU (Memorandum Of Understanding). However, until now there are some extortions in tourist areas by use government name. The purpose of this study is to de determine the extent of supervision in Danau Raja and to identify the obstacle factor towards overseeing Danau Raja tourism in Rengat, Indragiri Hulu, Riau Province.Based on the theory of Manullang, supervisory process of every objects are consists of phases, setting standards, conducting assessment and conduct corrective action the method of this study is descriptive qualitative with snowball sampling technique. The informants of this study are the Head of Tourism, Head of Development Section in tourist attraction and Head of tourist attraction charm, Pancasila Youth section, merchants and visitors.The result of the data analysis by descriptive qualitative, supervisory standards of Danau Raja carried out by the department based on the main objectives and functions that has been set, the action assessment made officially through the two officers who works to maintain the cleanliness of the tourism are of Danau Raja and it coordinates with the Organization of Pancasila Youth by used MOU authority to manages the entire facility of tourist attraction of Danau Raja along fee collection agency, then the government and The Organization of Pancasila Youth held a corrective action by conducting socialization and appeal to visitors or merchants in Danau Raja to maintain the environtment. There are several factors inhibiting the supervision of Danau Raja that are government regulations about tourism until now has not implemented, the lack of funds allocated for insfrastructure improvements, the lack of human resources professionals especially in the field of supervision as well as people who are less concerned to maintain the environment of danau Raja.Keywords: Supervision, Tourism, Danau Raja